As dinâmicas de uso e práticas do espaço público a partir das obras de reestruturação do Calçadão da Avenida Brasil em Cascavel - PR - Blanck, Priscila Laís (2020)
This research investigated the dynamics of appropriation of public spaces - the boardwalk of Brasil Avenue - after the last urban restructuring, concluded in 2019, adopting as a case study in the city of Cascavel - PR. Seeking to analyze the relationship of use and appropriation of space, through indirect systematic observation and the approach of user’s satisfaction. The main objective of this work was to analyze the transformation in the use and practices developed in the public space after the restructuring of the Brasil Avenue’s boardwalk under the focus of the potential that these spaces have to promote the population’s quality of life, being a study of the understanding of the city planning. The data collection was conducted by using document analysis techniques, indirect systematic observation, including physical surveys and questionnaires. The analysis of these data enabled greater precision and validation of the investigation, focusing on the importance of public spaces in the lives of the citizens of the city of Cascavel - PR, validating that the relationship between appropriation occurs between physical, natural and / or built aspects, allied to social interests, such as the users' wishes and intentions to manifest themselves favorable to the possibilities that the spaces offers, resulting in belonging bonds. Thus, the analysis of the public space on the boardwalk of Brasil Avenue based on the users’ behavior allowed to point out for the factors that have influence on the attractiveness’ potential and determine the intensity of use and the levels of satisfaction of the regulars.